2009
DOI: 10.1101/lm.1648509
|View full text |Cite
|
Sign up to set email alerts
|

Post-retrieval disruption of a cocaine conditioned place preference by systemic and intrabasolateral amygdala β2- and α1-adrenergic antagonists

Abstract: Previous work has demonstrated post-retrieval impairment in associative learning paradigms, including those mediated by drugs of abuse, using nonspecific b-adrenergic receptor (b-AR) antagonists. Remarkably little is known about the role of the specific b-AR subtypes, or other adrenergic receptors, in these effects. The current study examined the effects of b 1 and b 2 , as well as a 1 -adrenergic receptor antagonism following retrieval of a cocaine conditioned place preference (CPP). We found that rats admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 63 publications
(80 reference statements)
8
78
2
Order By: Relevance
“…Further, stimulating b 2 receptors in the prefrontal cortex can enhance working memory, while stimulating b 1 receptors impairs working memory (Ramos et al 2005(Ramos et al , 2008. Other mnemonic roles for b 2 signaling that have been recently described include reconsolidation and stress-induced reinstatement of conditioned place preference for cocaine (Bernardi et al 2009;Mantsch et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Further, stimulating b 2 receptors in the prefrontal cortex can enhance working memory, while stimulating b 1 receptors impairs working memory (Ramos et al 2005(Ramos et al , 2008. Other mnemonic roles for b 2 signaling that have been recently described include reconsolidation and stress-induced reinstatement of conditioned place preference for cocaine (Bernardi et al 2009;Mantsch et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although consistent with recent reports suggesting that β-adrenergic receptors do not mediate noradrenergic dependent real-time aversion , it is somewhat surprising that there was no effect in the CPA assay. Given the role of the BLA and β-adrenergic receptors in emotional and stressful memory (Bernardi et al, 2009;McGaugh, 2004;Wu et al, 2014), it is possible that our stimulus was not aversive or salient enough. Future studies could expand on the photostimulation parameters, and other learning assays, such as fear conditioning, may be more suited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LaLumiere et al (2010) found that repeated post-training administration of the b2-adrenergic agonist clenbuterol within the infralimbic cortex enhanced retention of extinction, as evidenced by lower responding in subsequent sessions. Other past work has found that interference with the NE system can disrupt stable memory formation as post-retrieval administration of propranolol can impair cocaine-conditioned place preference (Bernardi et al, 2006(Bernardi et al, , 2009Fricks-Gleason and Marshall, 2008) or conditioned reinforcement (Milton et al, 2008). These effects have been attributed to disrupted reconsolidation.…”
Section: Learning Consolidation and Reconsolidationmentioning
confidence: 99%
“…A role for NE in extinction learning has been demonstrated for extinction of conditioned fear (Cain et al, 2004;Morris and Bouton, 2007) and operant responding for food (Janak and Corbit, 2010). Similarly, recent studies found that NE is important for consolidation of extinction in both cocaine-conditioned place preference (Bernardi and Lattal, 2010;Bernardi et al, 2009;Brenhouse et al, 2010) and self-administration procedures (LaLumiere et al, 2010) using post-training administrations of adrenergic drugs. We hypothesized that the benefit to extinction produced by extinction of a compound cue may also rely on NE activity and, therefore, examined if extinction of cocaine seeking could be enhanced or impaired by pre-training manipulations of the NE system.…”
Section: Introductionmentioning
confidence: 99%